Growth and Physiology of Groundnut as Influenced by Micronutrients and Liming in Acid Soil of North East India - Das, Santanu; Das, Anup; GI, Ramkrushna; Layek, Jayanta; Chowdhury, Samik (Indian Journal of Hill Farming, 2017)
The field experiment was conducted in ICAR Research complex for NEH Region, Umiam, Meghalaya (980 m above mean sea level) in groundnut with six micronutrient treatments viz, control (no micronutrient), Zn @ 5 kg/ha, B @ 1 kg/ha, Mo @ 0.5 kg/ha, Zn + Mo, Zn + B + Mo (all the micronutrients were applied through soil application) and two soil amendment practices viz, lime @ 500 kg/ha (furrow application) and no lime. The objectives were to assess the effect of liming and micronutrient application on growth and physiological attributes of groundnut. Application of Mo produced significantly taller groundnut plants, dry matter/plant, nodule counts and weight/plant than control at all growing stages, which was at par with combined application of Zn + Mo and Zn + B + Mo. Liming significantly increased plant height, leaf area index, dry matter production, nodule weight and counts/plant than no liming. Application of micronutrients and liming also improved crop growth rate and relative growth rates of plant than those under control. Mo application alone registered significantly higher kernel yield (1720 kg/ha) than control (1316 kg/ha) and sole application of B (1624 kg/ha) and Zn (1562 kg/ha). The kernel yields obtained with integrated application of Zn + B + Mo and Zn + Mo were statistically similar to Mo alone. Furrow liming also enhanced the kernel yield (1756 kg/ha) significantly than that of no-liming (1511 kg/ha).